Carboxy-terminal polyglutamylation regulates signaling and phase separation of the Dishevelled protein - Kravec, Marek; Šedo, Ondrej; Nedvědová, Jana; Micka, Miroslav; Šulcová, Marie; Zezula, Nikodém; Gömöryová, Kristína; Potěšil, David; Sri Ganji, Ranjani; Bologna, Sara; Červenka, Igor; Zdráhal, Zbyněk; et al. (The EMBO journal, 2024)
Polyglutamylation is a reversible posttranslational modification that is catalyzed by enzymes of the tubulin tyrosine ligase-like (TTLL) family. Here, we found that TTLL11 generates a previously unknown type of polyglutamylation that is initiated by the addition of a glutamate residue to the free C-terminal carboxyl group of a substrate protein. TTLL11 efficiently polyglutamylates the Wnt signaling protein Dishevelled 3 (DVL3), thereby changing the interactome of DVL3. Polyglutamylation increases the capacity of DVL3 to get phosphorylated, to undergo phase separation, and to act in the noncanonical Wnt pathway. Both carboxy-terminal polyglutamylation and the resulting reduction in phase separation capacity of DVL3 can be reverted by the deglutamylating enzyme CCP6, demonstrating a causal relationship between TTLL11-mediated polyglutamylation and phase separation. Thus, C-terminal polyglutamylation represents a new type of posttranslational modification, broadening the range of proteins that can be modified by polyglutamylation and providing the first evidence that polyglutamylation can modulate protein phase separation.
Keywords: posttranslační úpravy proteinů; kyselina polyglutamová; protein dishevelled; Peptide Synthases; HEK293 Cells; Dishevelled 3; Dishevelled Proteins; TTLL11; Protein Condensates; lidé; Polyglutamylation; signální transdukce; Polyglutamic Acid; Protein Processing, Post-Translational; Phase Separation; Signal Transduction; Wnt Signaling Pathway; HEK293 buňky; fosforylace; signální dráha Wnt; Noncanonical Wnt Signaling; separace fází; Phosphorylation; peptidsynthasy; Humans